EP728 Targeted radiotherapy improves progression free survival and delays time to systemic therapy in limited relapse of ovarian cancer. (1st November 2019) - Kumar, A; Kapoor, A; Banerjee, S; Taylor, A; George, A; Gore, M; Lalondrelle, S
Abstract : Introduction/Background: Treatment for ovarian cancer (OC) usually involves systemic therapy (ST) and surgery. Radiotherapy (RT) is used for palliation, however for limited relapse may provide improved local control (LC) and defer the need for ST. We investigated the benefit of higher doses of RT in localised relapse of OC. Methodology: We performed a retrospective institutional review of patients with OC who received RT from 07/1998–12/2015. Radical prescription doses ≥30 Gy were included, palliative treatments <30 Gy and brain metastases were excluded. Data was collected to determine LC, progression free survival (PFS) and time to next ST (TNT) and correlated with lines of previous treatment, location of disease, histology, RT dose/fractionation, and platinum sensitivity. Results: 534 courses of RT for OC were identified. Of these, 65 courses in 59 patients (range 33–84 years)were eligible for inclusion. Histological subtypes were: serous (67.7%), endometrioid (12.3%), clear cell (6.1%), mucinous (6.1%), granulosa cell (3.07%), carcinosarcoma (3.07%) and borderline (1.5%). Table 1 shows the number of lines of previous ST. Table 2 show sites and modality of RT delivered. The median dose was 45Gy in 25# (range 33–64.8 Gy) for stereotactic treatments 30 Gy/3# (range 27–36 gy). Table 2 show sites and modality of RT delivered. The median dose was 45Gy in 25# (range 33–64.8 Gy) for stereotactic treatments 30 Gy/3# (range 27–36 gy). Conclusion: RT is underutilised and should be considered as an alternative to ST in limited relapse OC. Higher doses of RT can provide high rates of LC, improve PFS and delay time to ST in different histological subtypes and in heavily pre-treated patients. Disclosure: Nothing to disclose.